PENGARUH MODEL PEMBELAJARAN PROBLEM SOLVING BERBANTUAN MULTIMEDIA INTERAKTIF TERHADAP KETERAMPILAN GENERIK SAINS DAN HASIL BELAJAR SISWA PADA MATERI HIDROLISIS GARAM - Miftah Farid; Leny Leny (Universitas Lambung Mangkurat, 2016)
Abstract. This study aims to know the difference of science generic skills, students’ achievement, and student responds between class by applying of problem solving instructional model aided interactive multimedia and class by applying of problem solving instructional in SMA Negeri 1 Banjarmasin. This study applied quasy experiment method with nonequivalent control group design. Samples of this study are students of XI IPA 5 as experiment group and students of XI IPA 6 as control group. There are two variables in this study such as problem solving instructional model aided interactive multimedia as independent variable, science generic skills and students’ achievement as dependent variable. The experiment group applied problem solving instructional model aided interactive multimedia, while the control group applied problem solving instructional model. Data collection used test technique, observation, and questionnaires. Data were analyzed using t-test and descriptive analysis. T-test was used to analyzed differences of science generic skills and student cognitive achievement both experiment group and control group to determine the effect of problem solving instructional model aided interactive model. The results of this study that (1) there are not significantly difference of science generic skills between student of experiment group with control group, (2) there are significantly difference of student cognitive achievement between student of experiment group with control group, and (3) problem solving instructional model aided interactive multimedia received positive responds from student on the hydrolisis of salt material.Keywords: problem solving,interactive multimedia, students’ achievement, science generic skills